Mendorong Innovation Capability Pada Umkm: Peran Strategis Transformational Leadership Dan Knowledge Management Capability - Muzakki Muzakki; Ardiansyah Hendra Lukmana (Seminar Nasional Teknologi dan Multidisiplin Ilmu (SEMNASTEKMU), 2025)
This study examines the influence of Transformational Leadership (TL) on Innovation Capability (IC) with a particular emphasis on the mediating role of Knowledge Management Capability (KMC) among micro, small, and medium enterprises (MSMEs) in Surabaya. A quantitative approach employing an explanatory research design was adopted, wherein data were collected from 290 MSME actors across various business sectors through the distribution of structured questionnaires. The analytical procedure utilized Partial Least Squares–Structural Equation Modeling (PLS-SEM) with the aid of SmartPLS software to assess both the direct and indirect relationships among the variables under investigation. The empirical findings indicate that TL exerts a positive and significant effect on IC, illustrating that transformational leaders are capable of fostering an organizational climate conducive to creativity and innovative behavior. TL was also found to have a positive and significant impact on KMC, reinforcing the notion that transformational leaders play a strategic role in enhancing knowledge management processes through inspiration, intellectual stimulation, and effective collaboration. Moreover, KMC demonstrated a positive and significant influence on IC, underscoring its function as a critical mechanism that supports the development of innovation within MSMEs. The mediation analysis further confirms that KMC serves as a significant mediator in the relationship between TL and IC, indicating that effective knowledge management practices strengthen the influence of transformational leadership on innovation performance.